PENGARUH PEMAHAMAN KONSEPTUAL DAN DISPOSISI MATEMATIS TERHADAP HASIL BELAJAR SISWA KELAS X DI SMKN 1 UDANAWU BLITAR - Lutviana, Mufidatul (CV. Gerasi Insan Nusantara, 2023)
Factors that can affect students' mathematics learning outcomes include those related to students' ability to understand mathematical concepts and students' positive attitudes towards mathematics or commonly known as mathematical dispositions. The objectives of this study were (1) to determine the effect of conceptual understanding on the learning outcomes of class X students at SMKN 1 Udanawu (2) to determine the effect of mathematical dispositions on the learning outcomes of class X students at SMKN 1 Udanawu. (3) To determine the effect of conceptual understanding and learning outcomes on student learning outcomes in class X at SMKN 1 Udanawu. This study uses a quantitative approach to the type of non-experimental research, namely associative. The population in this study were all students of class X at SMKN 1 Udanawu. The sampling technique used in this study was purposive sampling with the research sample being class X BDP 3 consisting of 36 students. The data collection technique is by using questionnaires and tests. The analysis used by researchers is using simple linear regression analysis and multiple linear regression analysis. The results of this study indicate that (1) there is a significant influence between conceptual understanding on the learning outcomes of class X students at SMKN 1 Udanawu by 66.8%. (2) There is a significant influence between mathematical dispositions on the learning outcomes of class X students at SMKN 1 Udanawu by 33.2%. (3) There is a simultaneous significant effect between conceptual understanding and mathematical disposition on the learning outcomes of class X students at SMKN 1 Udanawu by 73.7%. Key words: Conceptual Understanding; Mathematical Disposition; Learning Outcomes